Structural feature of N-glycans of bamboo shoot glycoproteins: useful source of plant antigenic N-glycans. Issue 7 (3rd July 2017) - Tanabe, Chinatsu; Furuta, Kaori; Maeda, Megumi; Kimura, Yoshinobu
Abstract: An effective method to prepare plant complex type (PCT) N -glycans in large amounts has been required to evaluate their immunological activity. In this study, we found that glycoproteins in bamboo shoots predominantly carry PCT N -glycans including the Lewis a epitope-containing ones, suggesting that bamboo shoot is an excellent source for the plant antigenic glycans to synthesize immunoactive neoglycopolymers.